A modified differential evolution algorithm for frequency management of interconnected hybrid renewable system - Debayani Mishra; Manoj Kumar Maharana; Manoj Kumar Kar; Anurekha Nayak (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
In recent decades, the insufficiency in power production has led to the incorporation of renewable energy sources into microgrid systems. However, ambiguity in the generation of renewable sources and load variation impacts on the system frequency influencing the stable operation of microgrid system. To augment the stable operation of the system an intelligent controller is required for continuous electric power. The implementation of a modified differential evolution (MDE)-based cascaded PIDFN controller using ITAE is proposed in this work. In order to demonstrate the robustness and efficacy of the proposed MDE optimization technique is compared with DE, TLBO, IWO and PSO.MDE-based cascaded PIDFN controller is implemented for governing the frequency in two-area interconnected microgrid system. The system is substantiated over load perturbations, system uncertainties, communication delay and real time data of solar irradiance and wind speed and action of UPFC in MATLABÂ®/SIMULINK environment.